MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL CONGKLAK DI PAUD AL-ISTIQOMAH - Siti Az-Zahra, Fitreika; Dudin Abdul Latif, Asep; Zulvian Iskandar, Yogha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research was motivated by the low numeracy skills of children aged 5–6 years at PAUD Al-Istiqomah. The aim was to improve numeracy skills through the traditional congklak game using the Classroom Action Research (CAR) method by Kemmis and McTaggart with 12 children in group B as subjects. Data were collected through observation, interviews, and documentation. The findings revealed a significant improvement from the pre-cycle to cycle III, where 83% of the children achieved the categories of Developing as Expected and Very Well Developed. Thus, the congklak game proved to be effective and enjoyable as a learning medium to enhance early childhood numeracy skills.